Weak and strong cross section dependence and estimation of large panels - Alexander Chudik; Hashem Pesaran; Elisa Tosetti (European Central Bank (ECB), 2009)
This paper introduces the concepts of time-specific weak and strong cross section dependence. A double- indexed process is said to be cross sectionally weakly dependent at a given point in time, t, if its weighted average along the cross section dimension (N) converges to its expectation in quadratic mean, as N is increased without bounds for all weights that satisfy certain `granularity' conditions. Relationship with the notions of weak and strong common factors is investigated and an application to the estimation of panel data models with an infinite number of weak factors and a finite number of strong factors is also considered. The paper concludes with a set of Monte Carlo experiments where the small sample properties of estimators based on principal components and CCE estimators are investigated and compared under various assumptions on the nature of the unobserved common effects.
Keywords: C10; C31; C33; 330; Panels; Strong and Weak Cross Section Dependence; Weak and Strong Factors; Panel; Querschnittsanalyse; Korrelation; Zeitreihenanalyse; Theorie